"Des peines en général" in the French "Code pénal" of 1791 - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The publication is a continuation of the author’s studies on the history of judicial law of revolutionary France, with the author seeking to shed light on the sometimes underestimated first French criminal codification, adopted by the National Assembly in 1791. The researcher’s interests focus on the regulations determining the system of penalties adopted in the codification. Although the author’s dominant research method is exegesis of the normative text in the formal-dogmatic convention, the instruments of comparative legal studies have been used as well. Confronting the provisions of the code with the doctrinal assumptions and demands of the Enlightenment, the author seeks to show the complexity of multifaceted issues and specificity of the realities of revolutionary legislators, which necessitated compromises that are controversial for some researchers. Regardless of the critical remarks that have often been made about the French legislators, it is impossible to underestimate the crucial importance of the Code for the development of a European legal culture, which the author has tried to demonstrate by emphasising the pioneering nature of the law from the point of view of the development of new legal institutions.
Keywords: history of law; judicial law; criminal law; comparative legal studies; legal culture